Специфические особенности и возможности алмазно-искрового шлифования в микрогеометрической инженерии поверхности - Гуцаленко, Юрий Григорьевич; Аракелян, Арташес Арамескович (Лира, 2015)
In article questions of the formation of surface roughness in the presence of erosive microfracture treated surface under the action of electrical discharges in terms of a diamond-spark grinding are described. The possibilities of using the erosive effects of microvolume material removing from the treated surface in its microrelief smoothing are shown.
Keywords: эрозирование; инструмент режущий; обработка механическая; шероховатость; сглаживание; стружка